Pengaruh Gaya Kepemimpinan, Disiplin, Dan Pelatihan Terhadap Kinerja Pegawai Desa - Wulandari, Silvia; Hazizan, Halipi (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The progress of a village does not only depend on aspects of infrastructure and natural resources, but also very much depends on the quality of the human resources that manage it. This study aims to analyze how the aspects of leadership, discipline, and work motivation influence in ensuring that the performance of Cibuntu village employees reaches an optimal level. This research is descriptive quantitative using a sample of 70 employees in Cibuntu village, Cibitung sub-district, Bekasi Regency. The data collection method is through distributing questionnaires to respondents as the object of research. The data analysis technique uses multiple linear regression tests, hypothesis testing using the t test, f test, and the coefficient of determination test.  Through this study, researchers want to know whether leadership style, discipline, and training affect employee performance in Cibuntu village. From these problems, the results show that leadership style has a partially significant positive effect on employee performance, discipline partially has a significant positive effect on employee performance, and training partially has a significant effect on employee performance and leadership style, discipline, and training simultaneously have a significant effect on employee performance.